Performance of Islamic Microfinance Banks: The Case of a Developing Country - Akbar, Taufik; Nabiha, A.K Siti (KnE Social Sciences, 2019)
Similar to conventional microfinance banks institutions, Islamic microfinance banks provide intermediary financial services by receiving funds from investors and other stakeholders and disbursing funds to micro, small and medium-sized entrepreneurs and poor households. Islamic microfinance banks play a significant role in developing countries, especially in Indonesia. However, Islamic microfinance banks have not experienced significant growth and achieved good performance as expected. The paper thus investigates Indonesian Islamic microfinance banks performance in comparison to conventional microfinance banks. The data from the Indonesian Services Authority (OJK) were analyzed from 2012 to 2017. The findings showed that Islamic microfinance banks had performed poorly as compared to conventional microfinance banks. Suggestions for further empirical investigation were made to ascertain the reasons for such poor performance. Keywords: islamic microfinance banks, performance of islamic microfinance banks, indonesia, developing country.